Religiousness, religious coping methods and distress level among psychiatric patients in Malaysia - Mohamad Shariff, Nurasikin; A, Khatijah Aini; Musa, Ramli; S. A, Aida; N. Z, Zainal; C. G, Ng (International Journal of Social Psychiatry, 2012)
Background: Patients having psychiatric diagnoses often experience high level of distress. Religiousness is often used by them as part of their coping mechanism and problem-solving strategies. Objective: To determine the level of religious commitment and coping methods in psychiatric patients and its relationship with distress level. Methods: Religious commitment and coping patterns were measured with the Duke University Religious Index (DUREL) and Brief RCOPE, respectively. Psychopathology was assessed using the Brief Psychiatric Rating Scale (BPRS) and distress level was assessed with the Depressive, Anxiety and Stress Scale (DASS). Social support and experiences of recent threatening events were measured with the Multidimensional Scale of Perceived Social Support (MSPSS) and Life Threatening Events (LTE). Results: A total of 228 patients were included in this study with a mean age of 40.2 years. The majority were male, Malay, Muslim, single and with psychotic disorder. The subjects had a high level of religious commitment and had used more positive coping methods. Negative religious coping, psychiatric symptoms and diagnosis of anxiety disorder or major depression were significantly associated with high distress level. Higher religious commitment was significantly associated with lower distress (p < .05). Conclusion: Psychiatric patients were religiously committed and used more positive religious coping methods. Practices of negative religious coping, severe psychiatric symptoms and anxiety/depression were associated with higher distress.